Environmental taxation in the European Union: Are there common trends? - Francisco J. Delgado; Jaume Freire-González; Maria J. Presno (Economic Analysis and Policy, 2022)
Environmental taxation has been a permanent feature of the policy agenda over the past few decades. It has represented about 2.5 percent of GDP and 6 percent of total taxation in the EU in recent years. In this paper, we study the evolution of total environmental taxation and its two main subcategories, energy and transport taxes, as a percentage of GDP and as a share of total taxation in the EU, through a club convergence analysis of the period 1995–2016. From the GDP perspective, the results show three groups of countries or clubs for the total environmental taxation and only two clubs for the two other categories analysed. Considering the taxation structure perspective, two clusters emerge for the total environmental taxes, three for the energy case and only one for the transport taxation, denoting overall convergence in this case. These results indicate a high grade of convergence in environmental taxation in the EU.
Keywords: 330